Imagine the Future! A Critical Transreligious Bio-Theology of 'the 99 Percent'. (September 2013) - Auga, Ulrike
As reaction to the failures of the globalization process, which is based on a commodification of the whole life new resistance mobilizations occurred. The Occupy Wall Street Movement has underlined that the social consequences of the neoliberal empire call for new resistances, new visions of solidarity, and new ways of representation. It has become clear, that capitalism's influence on democracy has made that concept insufficient. The sovereign biopower is regulating life and survival via granting access or exclusion from resources. It not only disciplines and normalizes sexualities, bodies and gender but regulates health, security, etc. of everybody. Therefore responsible theology needs to expand Feminist, Gender and Queer critique and my approach is to offer a reaction by developing a critical Bio-Theology using Foucault's critique of biopower and Castoriadis' (1994) concept of the radical social imaginary. This paper uses inter- and transdisciplinary methodology bringing together (feminist) 'beyond liberation theology' approaches with queer, postcolonial, epistemological intersectionality critique and post-secular debates.